Selenium fundamentals : perform browser and web UI automation using Selenium. (Packt, 2018)
"We'll begin this course by understanding the importance of automating tests. Then, we will learn how to choose good selectors for navigating through your web application while highlighting best practices and techniques. After writing your first tests, you will go through the object model to help create your own advanced test cases. You will learn how to analyze a test report, track timing errors, and separate real issues from "flaky" tests. You will also learn how to configure and connect to a local grid, a network grid, and a third-party service. By the end of the course, you will have the skills you need to run automated tests on your own web application."--Resource description page